Effect of Thiourea as a Doping for Nanotitania - Rafidiyah, Nabilah (Journal of Technomaterial Physics, 2019)
Sulphur-doped TiO2 samples were prepared by sol gel method using thiourea as sulphur source. The amount of thiourea solutions are 0; 0.5; 1.0; 1.5 and 2 ml, respectively. Sulphur-doped TiO2 was calcinated at 450Â°C. Sulphur-doped TiO2 and pure TiO2 were characterized by X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM). Photo catalyst tests were carried out under sunlight and UV lamp. Based on XRD characterization, the samples are anatase phase. Furthermore, particle size was calculated using Scherrer equation and results of 8.94 and 12.98 nm, respectively for TBT-1.5 and TBT-0.5. TEM characterization showed that particle size of sulphur-doped TiO2 and pure TiO2 are 8.6 and 12.5 nm. Compared to TiO2 without doping, sulphur-doped TiO2 has a better photo catalyst activity for degradation of remazol golden yellow under visible light.